SOC Estimation of LiFePO4 Battery based on Improved Ah Integral Method - Zheng ZHU; Chongyang LIU; Dan LIU; Jinwei SUN (Institute of Advanced Engineering and Science, 2013)
State of charge (SOC) is the most important status parameters of energy storage system, which is able to predict the available mileage of electric vehicle. In fact, the accuracy of SOC estimation plays a vital role in the usability and security of the battery. To fully consider the practical demands, a novel method to predict SOC of LiFePO4 battery is presented in this paper, which defines the correct coefficient separately under two working conditions of charging and discharging. Based on effective factors such as coulombic efficiency, charge and discharge current, and temperature, an Ah integral SOC estimation method with two kinds of efficiency correct coefficients is established by performing massive experimental study. Experiments prove that the estimated error of SOC is less than 5%. Compared with the original Ah method, the improved Ah method is more advantageous in the accuracy and reliability. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3016